2010
DOI: 10.1111/j.1365-2427.2009.02374.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple stressors cause rapid ecosystem change in Lake Victoria

Abstract: SUMMARY1. Lake Victoria endured multiple stresses over the past century including population growth, increased cultivation of land, meteorological variability, resource extraction, intensive fishing, introduction of exotic species and more recently climate warming. These stressors became manifest through a fundamental and rapid change in the fish community and fishery in the early 1980s and visible eutrophication. However, the relation of these two phenomena and the possible interaction of the multiple stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
311
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(322 citation statements)
references
References 65 publications
11
311
0
Order By: Relevance
“…Based on paleolimnological analyses, changes in lower food web organisms began as early as the 1940s but accelerated dramatically through the 1960s and 1970s (Verschuren et al, 2002;Hecky et al, 2010). From the 1980s onwards, several studies have shown increased nitrogen and phosphorus loadings in the lake coinciding with decreased water transparency and oxygen levels (Mugidde, 1993;Hecky et al, 1994Hecky et al, , 2010Seehausen et al, 1997a;Verschuren et al, 2002). The eutrophication is thought to be caused by agricultural malpractices, urbanization and deforestation, although recent studies have suggested that climatic variability and wind stress played a crucial role as well (Kolding et al, 2008;Hecky et al, 2010;van Rijssel, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on paleolimnological analyses, changes in lower food web organisms began as early as the 1940s but accelerated dramatically through the 1960s and 1970s (Verschuren et al, 2002;Hecky et al, 2010). From the 1980s onwards, several studies have shown increased nitrogen and phosphorus loadings in the lake coinciding with decreased water transparency and oxygen levels (Mugidde, 1993;Hecky et al, 1994Hecky et al, , 2010Seehausen et al, 1997a;Verschuren et al, 2002). The eutrophication is thought to be caused by agricultural malpractices, urbanization and deforestation, although recent studies have suggested that climatic variability and wind stress played a crucial role as well (Kolding et al, 2008;Hecky et al, 2010;van Rijssel, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Based on paleolimnological analyses, changes in lower food web organisms began as early as the 1940s but accelerated dramatically through the 1960s and 1970s (Verschuren et al, 2002;Hecky et al, 2010). From the 1980s onwards, several studies have shown increased nitrogen and phosphorus loadings in the lake coinciding with decreased water transparency and oxygen levels (Mugidde, 1993;Hecky et al, 1994Hecky et al, , 2010Seehausen et al, 1997a;Verschuren et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beans complement the shortage of animal protein in East Africa, especially in the prevailing situation whereby fish production has been greatly impeded by the disastrous spread of water hyacinth in Lake Victoria (Ntiba et al, 2001;Hecky et al, 2010). The leguminous crop is also very important in agro-ecosystems, as it symbiotically fixes nitrogen through endophytic Rhizobium species (Bala et al, 2011;Devi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%